Effectiveness of the Supplementary Feeding Program on the Nutritional Status of Stunted Toddlers - Nurlathifah N. Yusuf; Nurul Fitriani; Siti Naili Ilmiyani; Supiani Supiani (GLOBAL HEALTH SCIENCE GROUP, 2024)
Providing additional food made from local food is one strategy for handling nutritional problems in toddlers and pregnant women. Lack of nutritious food intake in toddlers is one of the direct causes of toddler nutritional problems such as Stunting. So it is hoped that made from local food can encourage food independence and family nutrition in a sustainable manner. Aim to determine the effectiveness of providing local supplementary food on the nutritional status of stunted toddlers at Sekotong Health Center. Method: Pre-experimental research type with a one group pretest posttest design. The population, namely all stunted toddlers in October 2023, is 29 people. The sampling technique in this research was total sampling. The number of samples in this study was 29 people. Statistical tests use the Wilcoxon test. Results: The nutritional status of stunted toddlers before being given local was mostly in the Stunting category, as many as 20 people (69.0%). After being given, most of the Stunting category was 22 people (75.9%), with a mean value before of 1.69, while after being given the mean was 1.76. The Wilcoxon test results obtained a p value of 0.157 (p>0.05). There is no effectiveness of local on the nutritional status of stunted toddlers at Sekotong Health Center.